Functional Organization of Sequence Motifs in Diverse Transit Peptides of Chloroplast Proteins - Jeong, Jinseung; Hwang, Inhwan; Lee, Dong Wook (Frontiers in Physiology, 2021)
Although the chloroplasts in plants are characterized by an inherent genome, the chloroplast proteome is composed of proteins encoded by not only the chloroplast genome but also the nuclear genome. Nuclear-encoded chloroplast proteins are synthesized on cytosolic ribosomes and post-translationally targeted to the chloroplasts. In the latter process, an N-terminal cleavable transit peptide serves as a targeting signal required for the import of nuclear-encoded chloroplast interior proteins. This import process is mediated via an interaction between the sequence motifs in transit peptides and the components of the TOC/TIC (translocon at the outer/inner envelope of chloroplasts) translocons. Despite a considerable diversity in primary structures, several common features have been identified among transit peptides, including N-terminal moderate hydrophobicity, multiple proline residues dispersed throughout the transit peptide, preferential usage of basic residues over acidic residues, and an absence of N-terminal arginine residues. In this review, we will recapitulate and discuss recent progress in our current understanding of the functional organization of sequence elements commonly present in diverse transit peptides, which are essential for the multi-step import of chloroplast proteins.